Demuse: Releasing Stress Using Music Mobile Application - Aslina Baharum; Sakinah Ali Pitchay; Rozita Ismail; Noor Fzlinda Fabeil; Nordaliela Mohd Rusli; Iza Azura Ahmad Bahar (2018)
It can be seen that, conflicts, negative revolution, suicides, and other crimes becoming more common worldwide. Several studies and investigations have been conducted due to this case. Thus, it has been found that one of the root cause is stress, especially among the youth. Although stress can improve work performance and awareness for those who can manage it properly, however if someone is unable to cope with the stressful situation when it becomes excessive, the reaction might be disastrous. In tackling this unfavourable situation, several lifestyle changes have been prescribed such as listening to music, physical activities, doing desired activities, surfing, and others. This study uses the power of music to reduce stress. A mobile application named as “DeMuse” was developed and in its development, Mobile-D step-by-step methodology was applied. At explore phase, a number of existing applications have been compared. At the second phase, the initialize stage, a quantitative analysis was carried out to study the music and mood categories respectively. During the third and fourth phases, which were Productionize and Stabilise, the completion of Data Flow Diagram and Entity Relationship Diagram were established based on the quantitative analysis done. In the final phase, the System Test and Fix, the prototype were reviewed by 148 potential users. DeMuse showed to be one of the alternative ways to relieve stress. From this finding, DeMuse highlight the main feature which is the music and mood categories. In conclusion, DeMuse is a valid mobile apps that could be used to help reduce stress of its user. With this app, it hopes greatly to help in decreasing and eliminating the tension, dissatisfaction, and others negative feelings of users in their daily life.